2021
DOI: 10.3390/polym13152406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on Energy Consumption, Physical, and Mechanical Properties of Fused Deposition Modeling

Abstract: The application of the fused deposition modeling (FDM) additive manufacturing process has increased in the production of functional parts across all industries. FDM is also being introduced for industrial tooling and fixture applications due to its capabilities in building free-form and complex shapes that are otherwise challenging to manufacture by conventional methods. However, there is not yet a comprehensive understanding of how the FDM process parameters impact the mechanical behavior of engineered produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The thickness of the layer purely depends upon the extrusion nozzle diameter and must not exceed 80% of the nozzle diameter. [ 4 ] Therefore, to investigate the interaction of nozzle diameter with different layer heights for part strength, the present investigation includes nozzle diameters (0.4, 0.6, and 0.8 mm) with layer heights (0.20, 0.25, and 0.30 mm). In a study [ 30 ] triangular raster pattern has been suggested for bio‐implant/tissue 3D printed parts while comparing the mechanical response with grid and tri‐hexagonal raster pattern filled 3D parts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the layer purely depends upon the extrusion nozzle diameter and must not exceed 80% of the nozzle diameter. [ 4 ] Therefore, to investigate the interaction of nozzle diameter with different layer heights for part strength, the present investigation includes nozzle diameters (0.4, 0.6, and 0.8 mm) with layer heights (0.20, 0.25, and 0.30 mm). In a study [ 30 ] triangular raster pattern has been suggested for bio‐implant/tissue 3D printed parts while comparing the mechanical response with grid and tri‐hexagonal raster pattern filled 3D parts.…”
Section: Methodsmentioning
confidence: 99%
“…FDM method continuously faces a number of challenges due to its limitations with the mechanical strength of the part, surface quality, dimensional accuracy, and build time. [ 4 ] Thus, numerous researchers worked on improving the FDM process by developing new FDM feedstock materials, optimizing the FDM process parameters, analyzing the mechanical, thermal, and rheological behavior of build parts. In the FDM process, the feedstock filaments used can be nontoxic, biodegradable, and cost‐effective, thus, the FDM process is safe and eco‐friendly.…”
Section: Introductionmentioning
confidence: 99%
“…PHV can also influence the defects listed: Circularity, Geometrical accuracy, Surface Roughness, Shrinking, and Warping. [ 25 , 31 , 37 , 53 , 54 , 61 , 65 , 72 , 73 , 88 , 99 , 100 , 109 , 114 , 116 , 117 ] [ 32 , 34 , 36 , 68 , 71 , 76 , 92 , 106 , 108 , 112 , 118 ] Air Gap (AG) The measured lateral distance between the centre points of deposited adjacent filament strands. AG can also influence the defects listed: Geometrical accuracy, Porosity, and Surface Roughness.…”
Section: Printing Parameters and Their Impactmentioning
confidence: 99%
“…According to Enemuoh et al. [ 15 ], infill density, followed by layer height, print speed, and fill pattern, has high potential on the tensile strength of the FDM component. Christiyan et al.…”
Section: Introductionmentioning
confidence: 99%